Mitochondria-targeted cyclosporin A delivery system to treat myocardial ischemia reperfusion injury of rats - Zhang, Chang-xiong; Cheng, Ying; Liu, Dao-zhou; Liu, Miao; Cui, Han; Zhang, Bang-le; Mei, Qi-bing; Zhou, Si-yuan (Journal of nanobiotechnology, 2019)
Cyclosporin A (CsA) is a promising therapeutic drug for myocardial ischemia reperfusion injury (MI/RI) because of its definite inhibition to the opening of mitochondrial permeability transition pore (mPTP). However, the application of cyclosporin A to treat MI/RI is limited due to its immunosuppressive effect to other normal organ and tissues. SS31 represents a novel mitochondria-targeted peptide which can guide drug to accumulate into mitochondria. In this paper, mitochondria-targeted nanoparticles (CsA@PLGA-PEG-SS31) were prepared to precisely deliver cyclosporin A into mitochondria of ischemic cardiomyocytes to treat MI/RI. CsA@PLGA-PEG-SS31 was prepared by nanoprecipitation. CsA@PLGA-PEG-SS31 showed small particle size (~ 50 nm) and positive charge due to the modification of SS31 on the surface of nanoparticles. CsA@PLGA-PEG-SS31 was stable for more than 30 days and displayed a biphasic drug release pattern. The in vitro results showed that the intracellular uptake of CsA@PLGA-PEG-SS31 was significantly enhanced in hypoxia reoxygenation (H/R) injured H9c2 cells. CsA@PLGA-PEG-SS31 delivered CsA into mitochondria of H/R injured H9c2 cells and subsequently increased the viability of H/R injured H9c2 cell through inhibiting the opening of mPTP and production of reactive oxygen species. In vivo results showed that CsA@PLGA-PEG-SS31 accumulated in ischemic myocardium of MI/RI rat heart. Apoptosis of cardiomyocyte was alleviated in MI/RI rats treated with CsA@PLGA-PEG-SS31, which resulted in the myocardial salvage and improvement of cardiac function. Besides, CsA@PLGA-PEG-SS31 protected myocardium from damage by reducing the recruitment of inflammatory cells and maintaining the integrity of mitochondrial function in MI/RI rats. CsA@PLGA-PEG-SS31 exhibited significant cardioprotective effects against MI/RI in rats hearts through protecting mitochondrial integrity, decreasing apoptosis of cardiomyocytes and myocardial infract area. Thus, CsA@PLGA-PEG-SS31 offered a promising therapeutic method for patients with acute myocardial infarction.